Soil microbial carbon and nutrient constraints are driven more by climate and soil physicochemical properties than by nutrient addition in forest ecosystems. (February 2020) - Jing, Xin; Chen, Xiao; Fang, Jingyun; Ji, Chengjun; Shen, Haihua; Zheng, Chengyang; Zhu, Biao
Abstract: Soil enzymes produced by microorganisms transform substrates in the soil carbon (C) and nutrient cycles. Limitations in C and other nutrients could affect microbial biosynthesis processes, so we expect that soil enzyme activity will reflect microbial deficiencies in C, nitrogen (N) and phosphorus (P) at a large spatial scale. We collected soil from nutrient addition trials in eight forest ecosystems, ranging from temperate forests to tropical forests in eastern China, and conducted vector analysis of the soil enzymatic stoichiometry to examine the spatial extent of soil microbial C and nutrient limitations. We also determined whether nutrient addition could alleviate nutrient limitation or otherwise impact soil microbial resource use. Soil microbial C vs. nutrient limitation (thereafter C limitation) was greater in the temperate forests than in the tropical forests, but did not vary with soil depth. Soil microbial P vs. N limitation (thereafter nutrient limitation) decreased with latitude, and increased with soil depth. We found a negative relationship between soil microbial C limitation and nutrient limitation, which was more pronounced in the topsoil than in deeper soil depths. Furthermore, we found that climate (mean annual precipitation and temperature), soil pH and soil nutrients were significantly correlated with soil microbial C (explaining about 23% of the variation) and nutrient limitation (responsible for about 87% of the variation). Nutrient addition represented ~1% of the variation in soil microbial C and nutrient limitations and thus did not alleviate nutrient deficiencies. We conclude that soil microbial C and nutrient limitations are more likely driven by climate and soil physicochemical properties than by nutrient addition in eight forest ecosystems. Since soil microbial C and nutrient limitations result from long-term adaptation of soil microbial communities to site-specific soil and environmental conditions, the soil enzyme activity is not modified by short-term changes in nutrient availability resulting from fertilizer application. Highlights: Soil microbial C and nutrient limitations were studied across eight Chinese forests. Microbial C limitation increases with latitude, but does not change with depth. Microbial nutrient limitation decreases with latitude and increases with depth. Climate and soil properties were main drivers of microbial C and nutrient limitations. Nutrient addition does not alleviate soil microbial C and nutrient limitations.